Disembedding and re-embedding: the online interaction mechanisms of divorced youth in China - Wang, Junjie; Guo, Jialiang (Frontiers in Psychology, 2024)
China's rising divorce rates, notably among younger people, spotlight the shift in demographics undergoing this life transition and the need for research on their post-divorce social interactions. This study, through in-depth interviews with 19 young divorcees, explores their use of dating apps, applying Anthony Giddens' "disembedding" and "re-embedding" concepts to understand their online and real-world navigation. The findings reveal that these individuals face societal challenges, biases, and the residual effects of past marriages, leading them to seek refuge in online environments to avoid stigmatization. In digital spaces, they cautiously engage, revealing a lack of confidence through selective self-disclosure. Their goals range from forming same-sex and opposite-sex friendships to seeking new romantic relationships, indicating a nuanced approach to remarriage and challenging stereotypes of dating app users. Re-engaging online, they discover social support and a sense of community, which aids in regaining confidence post-divorce, underscoring the complex interplay between societal influences and individual adaptation strategies in the digital age.